The calculation of the maximum rate of oxidation of nitrogen (II) oxide using the mathematical package MathCad - Fatyeyeva, Anastasia; Ishchenko, Vera; Seidykh, Olga (My University, 2017)
In this paper, the problem of calculating the maximum oxidation rate of nitric oxide is considered.
Keywords: швидкість реакції; основний закон хімічної кінетики; математичного пакету MathCAD; скорость реакции; основной закон химической кинетики; математического пакета MathCAD; reaction rate; basic law of chemical kinetics; mathematical package MathCAD; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки